2021
DOI: 10.3390/s21186024
|View full text |Cite
|
Sign up to set email alerts
|

Tactile Object Recognition for Humanoid Robots Using New Designed Piezoresistive Tactile Sensor and DCNN

Abstract: A tactile sensor array is a crucial component for applying physical sensors to a humanoid robot. This work focused on developing a palm-size tactile sensor array (56.0 mm × 56.0 mm) to apply object recognition for the humanoid robot hand. This sensor was based on a PCB technology operating with the piezoresistive principle. A conductive polymer composites sheet was used as a sensing element and the matrix array of this sensor was 16 × 16 pixels. The sensitivity of this sensor was evaluated and the sensor was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 76 publications
0
23
0
Order By: Relevance
“…Therefore, this research develops object recognition for humanoid robots using full-hand tactile sensors, which achieves to carry and continues from our previous work [6].…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Therefore, this research develops object recognition for humanoid robots using full-hand tactile sensors, which achieves to carry and continues from our previous work [6].…”
Section: Introductionmentioning
confidence: 90%
“…The related work in object recognition by handling is quite diverse due to developments in several aspects of this subject, beginning with studies of human haptic behavior [7] from physiological and psychological studies to understand human haptic perception and unfamiliar objects surveys for recognition [8]. Other studies include humanoid robot hand system design to enable object handling [3], [4], [9], [10], control of the robot hand system of a humanoid robot [11], [12], tactile sensor array design for humanoids robot hand [5], [6], [13], [14], [15], [16], [17], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32]. Methods for recognizing objects based on tactile image recognition [6], [15], [18], [20], [21], [22], [23], [24], [28], [29], [31], [32], [33], [34], [35],…”
Section: Theory and Related Workmentioning
confidence: 99%
“…Piezo technology has been used for piezoresistive and piezoelectric tactile sensors for robot fingers and palms to recognise deformable and rigid objects [13], to detect slippage [14] and as array of sensors in robot hands for object recognition based on the object size and stiffness [15]. Tactile sensors with piezo technology are relatively easy to build, low cost, and can provide high sensitivity and high frequency.…”
Section: Related Workmentioning
confidence: 99%
“…In this process, using the method of manually defining features may result in losing important feature information, which may lead to a deviation in the results. However, many studies [ 25 , 26 , 27 , 28 ] have shown that deep learning algorithms play an important part in the tactile recognition of intelligent robots. The tactile recognition method, based on deep learning algorithms, can extract useful features from input vectors and greatly reduce the computational complexity [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%